Origin, Succession, and Control of Biotoxin in Wine - Xu, Xiaoyu; Li, Tian; Ji, Yanyu; Jiang, Xia; Shi, Xuewei; Wang, Bin (Frontiers in Microbiology, 2021)
Wine is a worldwide alcoholic beverage with antioxidant active substances and complex flavors. Moderate drinking of wine has been proved to be beneficial to health. However, wine has some negative components, such as residual pesticides, heavy metals, and biotoxins. Of these, biotoxins from microorganisms were characterized as the most important toxins in wine. Wine fermentation mainly involves alcoholic fermentation, malolactic fermentation, and aging, which endue wine with complex flavors and even produce some undesirable metabolites. These metabolites cause potential safety risks that are not thoroughly understood. This review aimed to investigate the origin, evolution, and control technology of undesirable metabolites (e.g., ochratoxin A, ethyl carbamate, and biogenic amines) in wine. It also highlighted current wine industry practices of minimizing the number of biotoxins in wine.